Frequency analysis of atrial electrograms identifies conduction pathways from the left to the right atrium during atrial fibrillation - studies in two canine models. - Ryu K; Sahadevan J; Khrestian CM; Stambler BS; Waldo AL (Journal of Cardiovascular Electrophysiology, 2009)
Studies of atrial fibrillation (AF) have demonstrated that a stable rhythm of very short cycle length in the left atrium (LA) can cause fibrillatory conduction in the rest of the atria. We tested the hypothesis that fast Fourier transform (FFT) analysis of atrial electrograms (AEGs) during this AF will rapidly and reliably identify LA-to-right atrium (RA) conduction pathway(s) generated by the driver. Methods and Results: During induced atrial tachyarrhythmias in the canine sterile pericarditis and rapid ventricular pacing-induced congestive heart failure models, 380-404 AEGs were recorded simultaneously from epicardial electrodes on both atria. FFT analysis of AEGs during AF demonstrated a dominant frequency peak in the LA (driver), and multiple frequency peaks in parts of the LA and the most of the RA. Conduction pathways from the LA driver to the RA varied from study-to-study. They were identified by the presence of multiple frequency peaks with one of the frequency peaks at the same frequency as the driver, and traveled (1) inferior to the inferior vena cava (IVC); (2) between the superior vena cava and the right superior pulmonary vein (RSPV); (3) between the RSPV and the right inferior pulmonary vein (RIPV); (4) between the RIPV and the IVC; and (5) via Bachmann's bundle. Conduction pathways identified by FFT analysis corresponded to the conduction pathways found in classical sequence of activation mapping. Computation time for FFT analysis for each AF episode took less than 5 minutes. Conclusion: FFT analysis allowed rapid and reliable detection of the LA-to-RA conduction pathways in AF generated by a stable and rapid LA driver.